You can take out an x
X(6x^2+5x-4)
Then factor it
X(3x+4)(2x-1)
Answer:
x = 6
Step-by-step explanation:
using Pythagoras' identity in the right triangle.
the square on the hypotenuse is equal to the sum of the squares on the other 2 sides , that is
x² + (x + 2)² = 10² ← expand parenthesis on left side and simplify
x² + x² + 4x + 4 = 100 ( subtract 100 from both sides )
2x² + 4x - 96 = 0 ( divide through by 2 )
x² + 2x - 48 = 0
(x + 8)(x - 6) = 0 ← in factored form
equate each factor to zero and solve for x
x + 8 = 0 ⇒ x = - 8
x - 6 = 0 ⇒ x = 6
however, x > 0 , then x = 6
Answer:
![x^2-7x+12](https://tex.z-dn.net/?f=x%5E2-7x%2B12)
Step-by-step explanation:
![(x-3)(x-4)=\\x \cdot x + x \cdot -4 +x \cdot -3 + -3 \cdot -4=\\x^2-4x-3x+12=\\x^2-7x+12](https://tex.z-dn.net/?f=%28x-3%29%28x-4%29%3D%5C%5Cx%20%5Ccdot%20x%20%2B%20x%20%5Ccdot%20-4%20%2Bx%20%5Ccdot%20-3%20%2B%20-3%20%5Ccdot%20-4%3D%5C%5Cx%5E2-4x-3x%2B12%3D%5C%5Cx%5E2-7x%2B12)
Hope this helps!
It’s LM becuase look at the photo Lm means